2013
DOI: 10.1242/dmm.012005
|View full text |Cite
|
Sign up to set email alerts
|

notch3is essential for oligodendrocyte development and vascular integrity in zebrafish

Abstract: SUMMARYMutations in the human NOTCH3 gene cause CADASIL syndrome (cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy). CADASIL is an inherited small vessel disease characterized by diverse clinical manifestations including vasculopathy, neurodegeneration and dementia. Here we report two mutations in the zebrafish notch3 gene, one identified in a previous screen for mutations with reduced expression of myelin basic protein (mbp) and another caused by a retroviral insertio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 91 publications
6
39
0
Order By: Relevance
“…S4A), whereas only notch3 fh332 mutant embryos exhibited cranial hemorrhage (supplementary material Fig. S4A), as recently reported (Wang et al, 2014;Zaucker et al, 2013). We also noted increased numbers of ISV endothelial cells only in embryos deficient for notch1b (supplementary material Fig.…”
Section: Multiple Notch Receptors and Ligands Contribute To Artery DIsupporting
confidence: 87%
See 1 more Smart Citation
“…S4A), whereas only notch3 fh332 mutant embryos exhibited cranial hemorrhage (supplementary material Fig. S4A), as recently reported (Wang et al, 2014;Zaucker et al, 2013). We also noted increased numbers of ISV endothelial cells only in embryos deficient for notch1b (supplementary material Fig.…”
Section: Multiple Notch Receptors and Ligands Contribute To Artery DIsupporting
confidence: 87%
“…Although combining genetic manipulation of Notch signaling with the tp1-driven transgenes has been helpful, generation of receptor-specific sensors, similar to NIP-Cre, or Gal4 fusions used successfully in Drosophila (Struhl and Adachi, 1998), will be needed moving forward. jh15 nred) jh15 ], notch1a tp37 , deltac tit446 , dll4 j16e1 and notch3 fh332 have been described elsewhere (Clements et al, 2011;Covassin et al, 2009;Holley et al, 2002;Jülich et al, 2005;Leslie et al, 2007;Parsons et al, 2009;Zaucker et al, 2013). Lines generated in this study are described below.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the small number of pericytes that develop in notch3 fh332 mutants is not sufficient to direct BBB formation, indicating that Notch3 function is part of a mechanism to promote adequate pericyte coverage of brain vessels. Notably, a recent study using independently identified notch3 hypomorphic alleles suggested that reduced Notch3 signaling compromised vascular tone and vascular integrity in the fins of adult zebrafish (Zaucker et al, 2013). Mural cells could not be unambiguously identified in the fin vasculature of notch3 mutants, supporting our own results.…”
Section: Research Articlesupporting
confidence: 70%
“…43 Another study showed that Notch3 regulates OPC development and myelin basic protein gene and maintains vascular integrity using zebrafish notch3 mutants. 44 Notch3 may have corresponding roles in OPC development and in encouraging vascular integrity, and also, there is a possibility that notch3 might comprise the communication between OPC and vascular cell. 44 …”
Section: Transgenic Mouse Lines For Cerebral Autosomal Dominant Artermentioning
confidence: 99%
“…44 Notch3 may have corresponding roles in OPC development and in encouraging vascular integrity, and also, there is a possibility that notch3 might comprise the communication between OPC and vascular cell. 44 …”
Section: Transgenic Mouse Lines For Cerebral Autosomal Dominant Artermentioning
confidence: 99%